2018
DOI: 10.3390/polym10050477
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Graphene Nanoplatelet Size and Surface Area on the AC Electrical Conductivity and Dielectric Constant of Epoxy Nanocomposites

Abstract: Epoxy nanocomposites reinforced with various grades of multilayer graphene nanoplatelets (GNPs) are manufactured and tested. The effects of size, surface area, and concentration of GNP, as well as alternating current (AC) frequency on the electrical and dielectric properties of epoxy nanocomposites are experimentally investigated. GNPs with larger size and surface area are always beneficial to increase the electrical conductivity of the composites. However, their effects on the dielectric constant are highly d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(45 citation statements)
references
References 70 publications
(87 reference statements)
1
34
0
Order By: Relevance
“…The electrical conductivity of the nanocomposites increased with increasing amount of GnP. The reason for this increase may have been that a greater number of electrons was conducted through the HDPE/GnP interface because frequency facilitated the hopping of electrons [20]. For the HDPE/G1 nanocomposites, no significant enhancement of the electrical conductivity was observed.…”
Section: Characterizationmentioning
confidence: 96%
See 1 more Smart Citation
“…The electrical conductivity of the nanocomposites increased with increasing amount of GnP. The reason for this increase may have been that a greater number of electrons was conducted through the HDPE/GnP interface because frequency facilitated the hopping of electrons [20]. For the HDPE/G1 nanocomposites, no significant enhancement of the electrical conductivity was observed.…”
Section: Characterizationmentioning
confidence: 96%
“…Numerous studies performed on nanocomposites with graphene or its derivatives have shown that the properties of nanocomposites depend on several factors, such as the polymer type, morphology, intrinsic properties, size and defect level of the filler material, production method, interface between filler and polymer, and others [10][11][12]. Although the size of GnPs is one of the most important factors, only few studies have investigated the size effect of GnPs on the properties of nanocomposites with various matrices, such as HDPE [13][14][15], polypropylene (PP) [8,9,16,17], epoxy [18][19][20], and polycarbonate (PC) [21] in the range of about 0.1-50 wt % (0.05-25 vol %). To the best of our knowledge, there has been no study on how the morphological, thermal, electrical, and mechanical properties of HDPEbased nanocomposites correlate with the size of GnPs in terms of thickness and lateral size.…”
Section: Introductionmentioning
confidence: 99%
“…It can be used to prepare a stacked two-dimensional graphene sheet ideal nano-filler to enhance the polymer matrix due to its good aspect ratio, unique two-dimensional structure, and low manufacturing cost [6,7]. Using the unique property of GNPs, previous studies have prepared films and conductive textiles with graphene/polymer-based composite with various graphene contents [8,9,10,11,12,13,14]. Hu et al [10] have prepared the graphene/PVDF films with a high-content of graphene, ranging from 40 wt% to 60 wt%, and found that the well-ordered layered structure was produced with the doctor-blading process.…”
Section: Introductionmentioning
confidence: 99%
“…Flexible antennas using graphene are promising due to their decent electrical conductivity and excellent mechanical properties. Graphene paper [ 31 ], graphene nanoflake ink [ 32 , 33 ], graphene oxide ink [ 34 ], and graphene nanoparticle ink [ 35 ] have been used in prior studies for fabricating flexible antennas. The performance of flexible antennas relies heavily on the fabricated conducting traces with high deformation sustainability while maintaining electrical conductivity [ 36 ].…”
Section: Materials For Flexible Antennasmentioning
confidence: 99%